MiR‐181a/b induce the growth, invasion, and metastasis of neuroblastoma cells through targeting ABI1. Issue 9 (16th June 2018) - Liu, Xiaodan; Peng, Hongxia; Liao, Wang; Luo, Ailing; Cai, Mansi; He, Jing; Zhang, Xiaohong; Luo, Ziyan; Jiang, Hua; Xu, Ling
Abstract : Neuroblastoma is a pediatric malignancy, and the clinical phenotypes range from localized tumors with excellent outcomes to widely metastatic disease in which long‐term survival is approximately 40%, despite intensive therapy. Emerging evidence suggests that aberrant miRNA regulation plays a role in neuroblastoma, but the miRNA functions and mechanisms remain unknown. miR‐181 family members were detected in 32 neuroblastoma patients, and the effects of miR‐181a/b on cell viability, invasion, and migration were evaluated in vitro and in vivo. A parallel global mRNA expression profile was obtained for neuroblastoma cells overexpressing miR‐181a. The potential targets of miR‐181a/b were validated. miR‐181a/b expression levels were positively associated with MYCN amplification and neuroblastoma aggressiveness. Moreover, ectopic miR‐181a/b expression significantly induced the growth and invasion of neuroblastoma cells in vitro and in vivo. Microarray analysis revealed that mRNAs were consistently downregulated after miR‐181a overexpression, leading to cell migration. In addition, the expression of ABI1 was suppressed by miR‐181a/b, and ABI1 was validated as a direct target of miR‐181a/b. We concluded that miR‐181a/b were significantly upregulated in aggressive neuroblastoma, which enhanced its tumorigenesis and progression by suppressing the expression of ABI1.